Pengaruh Ukuran Perusahaan, Struktur Modal, dan Corporate Social Responsibility Terhadap Kinerja Keuangan - Afridayani Afridayani; Irenne Putren (Universitas Muhammadiyah Palembang, 2025)
This research aims to determine the influence of company size, capital structure, and corporate social responsibility on financial performance. This type of research uses a quantitative approach with an associative type. The population of the study is companies in the basic materials sector listed on the Indonesia Stock Exchange during the period 2019-2023. The sampling technique used is purposive sampling. Hypothesis answers were obtained through panel data regression analysis using the statistical tool eviews 12. The results of the study indicate that company size and corporate social responsibility do not affect financial performance, while capital structure does affect financial performance.